KARAKTERISASI BAKTERI SELULOLITIK SIMBION RAYAP ASAL TAMAN NASIONAL BUKIT BAKA BUKIT RAYA, KALIMANTAN BARAT (Characterization of Cellulolytic Bacteria Termite Symbiont from Bukit Baka Bukit Raya National Park, West Kalimantan) - Hidayat, Mohamad Rusdi; Hidayati, Hidayati (Baristand Industri Banda Aceh, 2014)
Cellulase is the third largest industrial enzyme worldwide. This enzyme isproduced by microorganisms. Termite is one of the arthropods that could utilize symbioticmicroorganisms in their gut to digest lignocellulose. The purpose of this study was tocharacterize the cellulolytic bacteria that have been previously isolated from termites gutoriginated from the Bukit Baka Bukit Raya National Park. Isolates used were isolateMRH.13.S, isolate MRH.13.AF, and isolate MRH.13.O2. Characterizations conductedwere on the determination of the isolates growth curve, as well as the determination of theoptimum pH and temperature. The results showed that isolate MRH.13.S have an optimumtime at 36 hours. While isolate MRH.13.AF isolates had optimum time at 24 hours. Bothisolates have optimum pH in acidic conditions, and optimum temperature of 60ËC. Andisolates MRH.13.O2 have an optimum time of 48 hours, with an optimum pH in acidic toneutral and optimum temperature of 60ËC.